Save lives in the next pandemic: ensure vaccine equity now - Carlson, C.; Becker, D.; Happi, C.; O'Donoghue, Z.; Oliveira, T. de; Oyola, Samuel O.; Poisot, T.; Seifert, S.; Phelan, A. (Springer, 2024)
The proposed Pandemic Agreement must ensure that COVID-19 vaccine nationalism is never repeated; 290 scientists call for action.